2D Nanomaterials for Tissue Engineering and Regenerative Nanomedicines: Recent Advances and Future Challenges. Issue 7 (29th January 2021) - Zheng, Yuanyuan; Hong, Xiangqian; Wang, Jiantao; Feng, Longbao; Fan, Taojian; Guo, Rui; Zhang, Han
Abstract: Regenerative medicine has become one of the hottest research topics in medical science that provides a promising way for repairing tissue defects in the human body. Due to their excellent physicochemical properties, the application of 2D nanomaterials in regenerative medicine has gradually developed and has been attracting a wide range of research interests in recent years. In particular, graphene and its derivatives, black phosphorus, and transition metal dichalcogenides are applied in all the aspects of tissue engineering to replace or restore tissues. This review focuses on the latest advances in the application of 2D‐nanomaterial‐based hydrogels, nanosheets, or scaffolds that are engineered to repair skin, bone, and cartilage tissues. Reviews on other applications, including cardiac muscle regeneration, skeletal muscle repair, nerve regeneration, brain disease treatment, and spinal cord healing are also provided. The challenges and prospects of applications of 2D nanomaterials in regenerative medicine are discussed. Abstract : 2D nanomaterial‐based therapeutic strategies applied in tissue engineering and regenerative nanomedicines are discussed. Recent advances in the application of 2D nanomaterial‐based hydrogels, nanosheets, scaffolds, or drug delivery systems that engineered to repair skin, bone, cartilage, and other types of tissues are discussed along with the current challenges and future prospects.